MULTIMODALITY IN A PERFUME ADVERTISEMENT OF A FASHION MAGAZINE - Good Sumbayak Lingga; Siti Rahma Matondang; Alemina Br. Perangin-angin (Leksema: Jurnal Bahasa dan Sastra, 2021)
Getting information from magazine is the most favorite behavior of every people. Especially women want to know about many products such as perfume. On this occasion, the researcher tries to analyze the type of meaning contained in an advertising image, namely perfume products. Through analysis using multimodal, it will be found what meaning is contained in the image. The meaning content that will be examined are Representational, Interactive, and Composition. In an advertisement, of course, it will create attractive images or visuals in order to make buyers interested in the product. The product that will be analyzed in this research is perfume. Perfume is a product that both men and women are interested in. Because everyone wants to smell good at all times these days. In a conclusion, the many characteristics of the image will be summarized. What are the multimodal meanings included in the advertisement's product image?